1995
DOI: 10.1111/j.1476-5381.1995.tb16387.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of SCA40, NS 004 and NS 1619 on large conductance Ca2+‐activated K+ channels in bovine tracheal smooth muscle cells in culture

Abstract: 1 The effects of imidazopyrazine derivative, SCA40, on the activity of single large conductance, Ca2+-activated K+ (BKCa) channels in inside-out and outside-out patches from bovine tracheal smooth muscle (BTSM) BKCa channels when applied to either inside-out or outside-out BTSM patches, thus confirming that these compounds are activators of the BKCa channel in this preparation. 4 SCA40 (0.1 -10 pM) had no effect on the activity of BKCa channels when applied to either inside-out or outside-out patches which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Quinine is a relatively non-selective inhibitor among Ca+-dependent K+-channels (Haylett & Jenkinson, 1990 (Figure 4; Table 2). Further support for this idea comes from patch clamp experiments performed on bovine trachealis where SCA40 (0.1-10tM) failed to modify the activity of BKCa channels recorded from either inside-out, outside-out or cell-attached plasmalemmal patches (MacMillan et al, 1994).…”
Section: Resultsmentioning
confidence: 83%
“…Quinine is a relatively non-selective inhibitor among Ca+-dependent K+-channels (Haylett & Jenkinson, 1990 (Figure 4; Table 2). Further support for this idea comes from patch clamp experiments performed on bovine trachealis where SCA40 (0.1-10tM) failed to modify the activity of BKCa channels recorded from either inside-out, outside-out or cell-attached plasmalemmal patches (MacMillan et al, 1994).…”
Section: Resultsmentioning
confidence: 83%
“…Likewise, 6-keto PGF 1␣ synthesis by cultured retinal endothelial cells in response to SNP was nearly nullified by charybdotoxin and iberiotoxin but not by glibenclamide or 4-AP ( Figure 5C). In addition, the specific K Ca channel openers NS1619 and NS004 33 also stimulated synthesis of 6-keto PGF 1␣ ; this was virtually abolished by iberiotoxin. K ϩ channel blockers did not modify basal (in the absence of SNP, NS1619, or NS004) production of 6-keto PGF 1␣ .…”
Section: Role Of Pgi 2 Guanylate Cyclase and K Ca On No-induced Rementioning
confidence: 94%
“…Patch clamp studies have shown that in isolated smooth muscle cells from bovine trachea (21), rat portal vein (20), and basilar artery (22), NS1619 reversibly activates a hyperpolarising outward current resulting from the opening of BK Ca channels. A similar increase in the opening of BK Ca channels was seen in ventromedial hippocampal neurones (23).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the benzimidazolone compound, NS1619, has been shown to activate BK Ca channels in airways and vascular smooth muscle (20)(21)(22), and in hippocampal neurones (23). We have used this compound in combination with iberiotoxin, a highly selective blocker of BK Ca channels, to determine if the activation of these channels on sensory fiber endings in the guinea pig airways leads to an inhibition of fiber activity, using an in vitro model of single fiber recording (24).…”
Section: Introductionmentioning
confidence: 99%